Isolation and identification of Enterotoxigenic Escherichia coli (ETEC) from stools of Diarrheal Patients - Naznine, Farhana (BRAC University, 2010)
This thesis is submitted in a partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2008